Adopsi Teknologi Digital dalam Pariwisata di Indonesia dengan Model UTAUT3 - Supriyono; Ade Ananto Terminanto (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to investigate the technology usage behavior of tourists according to the modified acceptance and use of technology theory (UTAUT) model. Data were collected from a survey of 265 tourists using a random sampling technique. Partial least squares structural equation modeling (PLS-SEM) technique was used to analyze the data. The findings indicate that performance expectancy, hedonic motivation, and habit significantly influence tourists' behavioral intention to use information and communication technology, while effort expectancy, social influence, and facilitating conditions have no significant influence. However, actual usage behavior is highly dependent on tourists' behavioral intention and their habits, while facilitating conditions have no influence in this regard. The findings reveal the main factors influencing tourists' usage behavior that can help relevant stakeholders in designing tourism planning and marketing. The findings provide a strong contribution by extending the existing UTAUT-based literature by adding two new moderators in the relationship between behavioral intention and actual usage behavior.